Segmentation of plywood veneers as a pre-processing step in image analysis for material quality assessment - Gotardo, Cristian; Marini, Andreia; Ortoncelli, André Roberto (Anais da Escola Regional de Banco de Dados (ERBD); 2026: Anais da XXI Escola Regional de Banco de Dados, 2026)
The aesthetic quality of wood veneers is a decisive factor in adding value to the industry. Manual inspection presents limitations such as subjectivity and fatigue, motivating the use of Computer Vision. This study presents an approach to segment the veneer region in images collected in a real environment, aiming to adequately identify the area of interest for subsequent material quality classification. A YOLOv8 model trained for this purpose achieved a mAP@50 of 0.995 on the experimental database composed of 106 annotated images. Additionally, the model was qualitatively evaluated on 1,000 unlabeled images acquired under real operating conditions, yielding consistent, visually coherent segmentation results.